Geomechanical Classifications, Geotechnical Indexes, and Fractured Rock Media: the Influence of Discontinuities on the Rock Masses Description - Santa, Cláudio; Fernandes, Isabel; Chamine, Helder (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Using geotechnical indexes and geomechanical classifications is crucial in estimating the quality and behaviour of fissured rock masses. These tools play a significant role in large-scale engineering works, particularly in underground projects where the rock mass and its response to excavation are critical for project safety and financial feasibility. The widespread adoption of these classification systems in geoengineering necessitates continuous development and improvement to enhance accuracy and reliability and align them with the evolving construction landscape.
Keywords: geomechanical classifications; geotechnical indexes; discontinuities; rock mass